The Jewish Coins at Dura-Europos - Adler, Yonatan (Journal of ancient Judaism, 2021)
Abstract The synagogue at Dura-Europos is undoubtedly the most prominent of the Jewish remains uncovered at the site. Dozens of Jewish coins found in excavations throughout the city have merited far less attention. Alfred Bellinger published a list of these coins in 1949; among the corpus of 14,017 coins found altogether at the site, 47 were identified as coins minted in Judea by Jewish rulers. This study offers the first comprehensive presentation and analysis of these Jewish coins. Following a review and analysis of the limited data on all 47 Jewish coins published in the original report, a full report is presented for the six coins from the Dura collection which are currently housed at the Yale University Art Gallery. This is followed by a discussion about the possible reasons why such a large assemblage of Jewish coins found its way in antiquity from Judea to distant Dura-Europos.